2013
DOI: 10.1088/0957-0233/24/4/045901
|View full text |Cite
|
Sign up to set email alerts
|

A high-gshock tester with one-level velocity amplifier

Abstract: A simply constructed but efficacious shock tester is developed for screening or calibration of lightweight devices comprising micro-electro-mechanical systems (MEMS). The proposed shock tester provides a promising solution to the trade-off between cost-effective development and the demands on high-g shock testing devices. By incorporating material of high specific modulus and velocity gain achieved through collisions between vertically stacked masses, the shock tester achieves an acceleration range of about 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Driven by the technical demands of high-g shock tests and inspired by existing ideas, a compact high-g shock tester with a three-body vertically stacked shock amplifier was developed by the current authors. The experimental results confirmed that this design was successful [25][26][27] . However, a detailed study of the velocity amplification seems to have been deliberately ignored, most likely because the primary focus was on the shock acceleration pulse parameters.…”
supporting
confidence: 66%
“…Driven by the technical demands of high-g shock tests and inspired by existing ideas, a compact high-g shock tester with a three-body vertically stacked shock amplifier was developed by the current authors. The experimental results confirmed that this design was successful [25][26][27] . However, a detailed study of the velocity amplification seems to have been deliberately ignored, most likely because the primary focus was on the shock acceleration pulse parameters.…”
supporting
confidence: 66%
“…The first step towards building a deep learning model is to build a high-g shock test platform to generate the training data (shock signals) efficiently. There have been several types of shock test machines for generating high-g shocks [25]- [27]. Though these setups have respective advantage, such as generating higher g value, simple structure, and small size, they are too expensive and time-consuming to adapt to generate large scale data.…”
Section: A High-g Shock Test Systemmentioning
confidence: 99%
“…However, the maximum shock acceleration measured in these studies was only 1,000 G. For high-G accelerometer calibration, an enormous shock acceleration of at least tens of thousands of G is required to excite the accelerometer [3]. The ISO 16063-13 standard for high-G shock test or calibration methods is based on a device, such as a Hopkinson bar or air cannon, capable of producing a shock acceleration of 100 000 G or more [1]. A significant shock can introduce much noise into the LDV signal, making demodulation difficult and reducing measurement accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…High-G accelerometers are widely used in fields such as weapons and ammunition because they can measure high shock signals [1][2][3]. To improve the measurement accuracy of high-G accelerometers, it is always necessary to calibrate them [4,5].…”
Section: Introductionmentioning
confidence: 99%